P152 Prediction of Death or Heart Failure-related Hospitalizations by Cardio-ankle Vascular Index (CAVI) and CAVI0 - Bart Spronck; Jonathan Lee; Garrett Oldland; Mary Jo Obeid; Mahati Paravathaneni; Naga Vaishnavi Gadela; Armghan Ans; Gurpreet Singh; Rushik Bhuva; Scott Akers; Julio Chirinos (Artery Research, 2020)
Background: Arterial stiffness as measured by carotid-femoral pulse wave velocity (PWV) has been shown to predict cardiovascular events [1]. However, PWV is blood pressure (BP) dependent [2,3] leading to the development of cardio-ankle vascular index (CAVI) as a more blood pressure-independent index [4] that also shows predictive ability in Asian populations [5]. Recently, CAVI was further refined into CAVI0 [6], removing residual acute blood pressure dependence [7]. The present study aims to assess risk prediction by CAVI and CAVI0 in a US population. Methods: We enrolled 156 subjects (94.8% male; 47.7% African-American) with and without heart failure. Subjects underwent arterial stiffness assessments (VaSera 1500 N, Fukuda Denshi Co., Tokyo, Japan). Left (L-CAVI) and right (R-CAVI) measurements were obtained from the device, CAVI0’s were converted from CAVI’s taking into account CAVI’s scale coefficients [8,9]. We prospectively followed participants for a mean of 2.56 years for the composite endpoint of death or heart failure related hospital admission. Results: L-CAVI and R-CAVI did not differ significantly (9.80 ± 2.11 vs 9.66 ± 1.92, p = 0.146); neither did L- CAVI0 and R-CAVI0 (16.51 ± 5.85 vs 16.15 ± 5.34, p = 0.178). In unadjusted Cox regression, R-CAVI, L-CAVI, and R-CAVI0 but not L-CAVI0 predicted outcome (Table 1). After adjustment for age, sex, race, and systolic BP, only right-sided CAVIs and CAVI0s were predictive. TableCox regression results